Application of Sepsis Definitions to Pediatric Patients Admitted With Suspected Infections in Uganda*. Issue 5 (May 2016) - Wiens, Matthew O.; Larson, Charles P.; Kumbakumba, Elias; Kissoon, Niranjan; Ansermino, J. Mark; Singer, Joel; Wong, Hubert; Ndamira, Andrew; Kabakyenga, Jerome; Moschovis, Peter; Kiwanuka, Julius
Abstract : Objectives: Acute infectious diseases are the most common cause of under-5 mortality. However, the hospital burden of nonneonatal pediatric sepsis has not previously been described in the resource poor setting. The objective of this study was to determine the prevalence of sepsis among children 6 months to 5 years old admitted with proven or suspected infection and to evaluate the presence of sepsis as a predictive tool for mortality during admission. Design: In this prospective cohort study, we used the pediatric International Consensus Conference definition of sepsis to determine the prevalence of sepsis among children admitted to the pediatric ward with a proven or suspected infection. The diagnosis of sepsis, as well as each individual component of the sepsis definition, was evaluated for capturing in-hospital mortality. Setting: The pediatric ward of two hospitals in Mbarara, Uganda. Patients: Admitted children between 6 months and 5 years with a confirmed or suspected infection. Interventions: None. Measurements and Main Results: One thousand three hundred seven (1, 307) subjects with a confirmed or suspected infection were enrolled, and 65 children died (5.0%) during their admission. One thousand one hundred twenty-one (85.9%) met the systemic inflammatory response syndrome criteria, and therefore, they were defined as having sepsis. The sepsis criteria captured 61 deaths, demonstrating a sensitivity and a specificity of 95% (95% CI, 90–100%) and 15% (95% CI, 13–17%), respectively. The most discriminatory individual component of the systemic inflammatory response syndrome criteria was the leukocyte count, which alone had a sensitivity of 72% and a specificity of 56% for the identification of mortality in hospital. Conclusions: This study is among the first to quantify the burden of nonneonatal pediatric sepsis in children with suspected infection, using the international consensus sepsis definition, in a typical resource-constrained setting in Africa. This definition was found to be highly sensitive in identifying those who died but had very low specificity as most children who were admitted with infections had sepsis. The systemic inflammatory response syndrome–based sepsis definition offers little value in identification of children at high risk of in-hospital mortality in this setting.